(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2007)
This study is part of a doctoral research project aimed at elaborating and evaluating a behavior management intervention program for foster care staff working with victimized children. The original study involved 14 workers, but the specific objective here involves analyzing the interaction of two caregivers with the two children along the intervention program. The results demonstrated that the frequency of positive interaction of caregivers and children’s increased and of coercitive interaction reduced as well. These results possibly demonstrate that attention maintained procedures to diminish the frequency of children’s inadequate behaviors, and the ones aimed at increasing the frequency of the adequate behaviors compete with coercitive interaction standards between caregiver and child and, therefore produce an immediate decrease.